2016
DOI: 10.1128/jvi.02531-15
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus gp350 Can Functionally Replace the Rhesus Lymphocryptovirus Major Membrane Glycoprotein and Does Not Restrict Infection of Rhesus Macaques

Abstract: Primary Epstein-Barr virus (EBV) infection is the most common cause of infectious mononucleosis, and persistent infection is associated with multiple cancers. EBV vaccine development has focused on the major membrane glycoprotein, gp350, since it is the major target for antibodies that neutralize infection of B cells. However, EBV has tropism for both B cells and epithelial cells, and it is unknown whether serum neutralizing antibodies against B cell infection will provide sufficient protection against virus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Alternatively, the virus may initially infect infiltrating B cells, which would lead to subsequent targeting of epithelial cells. Neither scenario is mutually exclusive; thus a combination of epithelial and B cell neutralizing antibodies may be required to most effectively block incoming virus at the oral mucosa (Herrman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the virus may initially infect infiltrating B cells, which would lead to subsequent targeting of epithelial cells. Neither scenario is mutually exclusive; thus a combination of epithelial and B cell neutralizing antibodies may be required to most effectively block incoming virus at the oral mucosa (Herrman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…pCAGGS expression plasmids for gH, gL, gB, and pT7EMCLuc (which carries a luciferase-containing reporter plasmid under the control of the T7 promoter) were kindly provided by Dr. R. Longnecker (Haan et al, 2001; Okuma et al, 1999; Plate et al, 2011). Plasmids for the expression of humanized, recombinant 72A1 were provided by Dr. F. Wang (Herrman et al, 2015). p509, an expression plasmid encoding BZLF1, was provided by Dr. W. Hammerschmidt (Delecluse et al, 1998).…”
Section: Methods Detailsmentioning
confidence: 99%
“… 53 The 72A1 mAb, which showed protection in mice, does not cross-react with the rhesus gp350 protein. 54 A chimeric rhLCV virus expressing gp350 from EBV is infectious in macaques and susceptible to neutralization by 72A1, 54 but passive transfer studies of neutralizing mAbs against rhLCV have not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to undertaking the humanization of mouse (m)72a1, we re-examined the reported differences in anti-gp350 reactivity observed with the use of antibody constructs based on two separate sets of m72a1 variable region (VR) cDNAs [ 33 , 34 ]. An examination of archived chimeric antibody samples generated in our laboratory prior to our earlier publication showed that the strongest anti-gp350 immunoreactivity was found in a chimeric antibody based on GenBank cDNA sequences KT211017.1 and KT211018.1 ( Figure S1 ) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The murine 72a1 HC partial coding sequence (GenBank KT211017.1) [ 34 ] was modified by addition of the Bam HI restriction enzyme recognition site upstream of the HC VR ATG start sequence and the introduction of a Sca I site at nucleotide position 409 ( DNA sequence S1 ). The murine 72a1 lambda LC partial coding sequence (GenBank: KT211018.1) [ 34 ] was modified to remove an internal Sca I restriction enzyme site at nucleotide position 133 and restriction enzymes Hind III and Hinc II introduced upstream of the LC ATG start sequence and at nucleotide 372, respectively ( DNA sequence S2 ). Nucleotide modification to introduce new restriction enzyme sites was not expected to change the 72a1 protein sequences.…”
Section: Methodsmentioning
confidence: 99%